2010
DOI: 10.1021/la102304m
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of New TPD Analysis Techniques in the Evaluation of Second Order Desorption Kinetics of Cyanogen from Cu(001)

Abstract: The interactions of cyanide species with a copper (001) surface were studied with temperature programmed desorption (TPD) and X-ray photoelectron spectroscopy (XPS). Adsorbed cyanide species (CN(a)) undergo recombinative desorption evolving molecular cyanogen (C(2)N(2)). As the adsorbed CN species charge upon adsorption, mutually repulsive dipolar interactions lead to a marked desorption energy reduction with increasing CN(a) coverages. Two new TPD analysis approaches were developed, which used only accurately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Cyanogen (CN) 2 was not observed. 37 Note that the gradual monotonic increase of the H 2 TD signals (i.e. not the peaks) is due to a general increase of the partial pressure due to warming-up of the sample holder.…”
Section: Page 8 Of 27 Acs Paragon Plus Environment the Journal Of Phymentioning
confidence: 99%
“…Cyanogen (CN) 2 was not observed. 37 Note that the gradual monotonic increase of the H 2 TD signals (i.e. not the peaks) is due to a general increase of the partial pressure due to warming-up of the sample holder.…”
Section: Page 8 Of 27 Acs Paragon Plus Environment the Journal Of Phymentioning
confidence: 99%
“…Later experimental studies [8] identified that the surface coverage of CN fragments Table 2 Nearest-neighbour distances between ion cores in the c(10 × 6)-CN/Cu(0 0 1) system shown in Fig. 2(a).…”
Section: Results and Analysismentioning
confidence: 99%
“…This allowed division of the unreconstructed c(10 × 6)-Cu(0 0 1) into a 'checkerboard' of 30 four-fold sites which were populated by 12 CN fragments in the optimal structure. The range of possible binding sites was reduced by invoking the experimentally observed c2 mm symmetry [7] of the system and the experimental observation that the CN fragments occupy equivalent binding positions [8]. The sequence was repeated using both the local density approximation (LDA) and the generalised gradient approximation (GGA) to describe the density functional.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations